R. W. Van Olsteen and Fight Against American Uniqueness: Historiography of Genesis of US Foreign Policy in 1940s — 1960s - D. V. Dorofeev (Научный диалог)
The relevance of the study is due to the low degree of study of the revisionist historian R. W. Van Olsteen views in historiography. The purpose of the article is to concretize the scientist’s views on the genesis of US foreign policy. The scientific novelty of the work lies in the creation of a conceptual framework for the intellectual biography of the researcher and determination of his assessment of the emergence of the United States foreign policy. The methodological complex of research consists of two levels: the first includes the principles of historicism, objectivity, consistency, the second — historical-chronological, historical-biographical, descriptive and prosopographic methods. A tendentiousness in the concept of the scientist is established in the article: throughout his career, he debunked the myth of American uniqueness. In this context, R. W. Van Olsteen considered the emergence of US foreign policy, which he associated exclusively with the British experience. It is proved that initially the scientist based his assessment on political realism (late 1930s — mid 1940s); and in a later period — a synthesis of history, political science and psychology (late 1940s — 1960s). The author revealed the failure of the historian’s theoretical developments and established the secondary nature of his assessment of the emergence of US foreign policy. The research results are focused on their application in the study of the history of the North American state.